Students' Learning Outcomes in Organic Chemistry Using Edpuzzle via Google Classroom - Dedi Irwandi; Pardiana Pardiana; R Ahmad Zaky El Islami (Jurnal Pendidikan MIPA, 2026)
This study aims to describe and analyze students' learning outcomes in the Organic Chemistry 1 course after the implementation of Edpuzzle-based interactive learning videos delivered through Google Classroom, and to examine the consistency of individual academic performance across two summative assessment points. A quantitative descriptive design was employed involving 52 undergraduate students enrolled in the Chemistry Education Program during the 2025/2026 Academic Year, consisting of Class A (n = 27) and Class B (n = 25). Four instructor-developed Edpuzzle videos (approximately 110 minutes in total) covering the topic of Atoms and Molecules were distributed via Google Classroom without embedded interactive checkpoints; the videos were designed for continuous, uninterrupted viewing. Learning outcomes were measured using essay-based Midterm (UTS) and Final (UAS) examinations, both of which were empirically validated and reliable (α = 0.801–0.882). Data were analyzed through descriptive statistics, the Shapiro-Wilk normality test, and correlation analysis (Pearson for Class A; Spearman for Class B). The results show that mean scores for Class A were 49.22 (UTS) and 43.52 (UAS), while Class B obtained 39.36 and 33.12, respectively, all below the institutional passing threshold. A strong positive UTS–UAS correlation was found in Class A (r = 0.822, p < 0.001) and Class B (r_s = 0.788, p < 0.001), indicating high relative rank-order stability of individual academic standing across the two assessment periods, rather than consistency of Organic Chemistry concept mastery (the two instruments differ in content domain and difficulty) or a causal effect of Edpuzzle. Interpreted through Mayer's Cognitive Theory of Multimedia Learning, the findings suggest that interactive video alone is insufficient to manage the intrinsic cognitive load of Organic Chemistry content. The study implies the need for structured video-based instructional designs integrating active learning, formative feedback loops, and early academic intervention for underperforming students. Keywords: edpuzzle, video-based learning, learning outcomes, organic chemistry, cognitive theory of multimedia learning.